The Shoe Industry of Marikina City, Philippines: A Developing-Country Cluster in Crisis - Scott, Allen J. (Kasarinlan: Philippine Journal of Third World Studies; Vol 20 No 2 (2005): International Political Economy, 2007)
This study describes the main features of the shoe industry in the Philippines, the core of which is located in Marikina City in the northeast of the Manila Metropolitan Area. Initial discussions delve with general remarks on industrial clusters and commodity chains with a detailed account of their internal structure and changing fortunes. The deeply-rooted failures of the cluster since the early 1990s are pinpointed. These can be directly related to the liberalization of the Filipino economy, and the concomitant increase in Chinese-made shoes on domestic markets. Various private and public responses to the crisis are described and evaluated. It is argued that as helpful as many of these responses may be, their overall impact is likely to remain limited. Series of possible policy options and their high risks of failure are emphasized. In conclusion, the study presents a developmental scenario based on cluster upgrading and intensified export activity.
Keywords: shoe industry; Marikina city; commodity chains; trade liberalization; vertical disintegration; globalization